POÉTICA DEL CUENTO DECADENTE - De Diego, Rosa (Anales de Filología Francesa, 2006)
“Poetics of the decadent story” is an analyse of the cruel decadent story of the end of the century beginning with “Histoires désobligeantes” by Léon Bloy. The decadent story is a testimony about the psychology and habits of the decadent period. It’s an observation document which talks about probable and real stories, in the naturalist line. But the whole represents as well an accusative judgement about materialist ideas. In for or five pages Bloy concentrates all the magnitude and terror of a drama which acquires a parable’s meaning because of this reduction nearly caricatured.